2016
DOI: 10.1002/rcm.7724
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of metformin by‐products under photolysis, photocatalysis, ozonation and chlorination by high‐performance liquid chromatography coupled to high‐resolution mass spectrometry

Abstract: It is also observed that all systems exhibited low mineralization rates, with the chlorination process being slightly more efficient in promoting the degradation, whereas the ozonation was more efficient in promoting the mineralization of metformin. Based on these results a route for the chlorination, photodegradation and ozonation of MTF, which comprised of its successive oxidation in the aqueous medium, could be proposed. It could also be concluded that the treated samples were not cytotoxic to HepG2 cells i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 28 publications
(37 reference statements)
1
33
0
Order By: Relevance
“…It is noteworthy to mention that DMG was reported to be a major product of the transformation of the MF during chlorine disinfection of water. 15,18 Some of these products, unfortunately, are hazardous, such as hydroxyacetonitrile (known as glycolonitrile) and NDMA. The latter is a common by-product of many wastewater treatment processes.…”
Section: Gcms Analysis Of Oxy-cracking Productsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy to mention that DMG was reported to be a major product of the transformation of the MF during chlorine disinfection of water. 15,18 Some of these products, unfortunately, are hazardous, such as hydroxyacetonitrile (known as glycolonitrile) and NDMA. The latter is a common by-product of many wastewater treatment processes.…”
Section: Gcms Analysis Of Oxy-cracking Productsmentioning
confidence: 99%
“…Despite its popularity, MF cannot be metabolized by the human body and it is estimated that 70% of this drug is excreted in the urine and faeces. [15][16][17] For this reason, considerable amounts (up to 100 ppm) of the drug was detected in WTTPs effluents in many places worldwide. 15,18,19 Recent studies showed that MF was proven to pose ecological risks to aquatic life with concentration levels close to those detected in surface water.…”
Section: Introductionmentioning
confidence: 99%
“…For the ozonation experiments, a O 3 solution was prepared by continuously bubbling gaseous ozone, produced by an O 3 generator, in ultrapure water, until the medium was enriched at 9 mg/L of the O 3 . A standard curve ([O 3 ] (mg/L) = 14.59 × Absorbance) for the determination of ozone concentration by UV spectrophotometric (260 nm) was made by the Indigo Carmine method (sodium indigodisulfonate, C 16 H 8 N 2 Na 2 O 8 S 2 ) considering the molar absorptivity of 3290 M −1 cm −1 . The experiments were performed in closed amber flasks, 20 mL capacity, and with the aid of magnetic stirrers.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 3 shows these two pathways for degradation of metformin. Different processes induced the degradation of metformin, i.e., direct photolysis (UVC), photocatalysis (TiO2/UVC), ozonation, and chlorination, in the study of Quintao et al [35]. Subsequently, all of the samples were analyzed by LC/HRMS, by which five products were detected, and the molecular formulae for all of them were proposed.…”
Section: Identification Of Degradation Productsmentioning
confidence: 99%